2019
DOI: 10.1186/s13063-019-3352-1
|View full text |Cite
|
Sign up to set email alerts
|

POPPIE: protocol for a randomised controlled pilot trial of continuity of midwifery care for women at increased risk of preterm birth

Abstract: Background High rates of preterm births remain a UK public health concern. Preterm birth is a major determinant of adverse infant and longer-term outcomes, including survival, quality of life, psychosocial effects on the family and health care costs. We aim to test whether a model of care combining continuity of midwife care with rapid referral to a specialist obstetric clinic throughout pregnancy, intrapartum and the postpartum period is feasible and improves experience and outcomes for women at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
0
12
0
4
Order By: Relevance
“…This study is reported as per the CONsolidated Standards of Reporting Trials (CONSORT) ( S1 CONSORT Checklist). There were no substantial changes to the published study design [ 22 ] after commencement of the trial.…”
Section: Methodsmentioning
confidence: 99%
“…This study is reported as per the CONsolidated Standards of Reporting Trials (CONSORT) ( S1 CONSORT Checklist). There were no substantial changes to the published study design [ 22 ] after commencement of the trial.…”
Section: Methodsmentioning
confidence: 99%
“…The main POPPIE trial paper is described in detail elsewhere [19], but in brief, this study used a two-arm hybrid implementation-effectiveness, randomised, controlled pilot trial within an inner-city teaching hospital in the UK between, to compare midwifery continuity of care (POPPIE group) with standard maternity care (standard group) for women identified at increased risk of PTB. Pregnant women attending for antenatal care at less than 24 weeks' gestation were eligible if they were considered at risk of preterm birth (e.g.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Middle‐range theories are helpful to conceptualize complex reality so that explanations of findings become possible and generalizable 14 . This conceptualization can also inform the analysis of ongoing studies evaluating continuity models of care for women at increased risk of PTB 19 …”
Section: Methodsmentioning
confidence: 99%